Pendidikan Karakter di Sekolah Menengah Kejuruan (Studi Kasus Pembelajaran IPS di SMK se-Kecamatan Margoyoso Pati) - Karim, Abdul; Susilowati, Retno; Muslim, Muslim (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2021)
This study aims to describe the character education in SMK in Margoypso District. The type of research is descriptive qualitative research. Collecting data by using interviews, observation and documentation. The data analysis uses data collection steps, data reduction, data presentation and drawing conclusions. The results of the study show that: The media used in character education for students in Vocational High Schools in Margoyoso District are: 1) Exemplary Media; 2) Habituation Media; 3) Meditation/dhikr; 4) Indoctrination; 5) Behavior / Personality. The study found that all teachers had (1) a steady personality, (2) a stable personality, (3) mature, and (4) wise because the learning time in the class of students could be conditioned. It's just that there are still some students who seem anxious or not focused in the learning process in class.